Judge's Rejection of Compensation for the Management of Dowry Disputes (Analysis of Decision Number 262/Pdt.G/2022/Pa.Batg) - Nasution, Muhammad Iqbal Hanafi; Iwan, Iwan (Jurnal Daulat Hukum, 2024)
This study raises the case of a judge's rejection of a claim for compensation for the management of a dowry dispute at the Bantaeng Religious Court. The case involved a couple who separated after the husband took back the land that had previously been used as dowry. Although the judge decided to return the land to the wife, the judge rejected the wife's claim for compensation for the management of the land. In this context, the rule of Al'adatu Muhakkamah is one of the principles used in determining the law when there is no shar'i evidence that explicitly explains it. This study aims to analyze the judge's decision to refuse compensation for the results of the management of the dowry dispute and analyze the use of the Al'adatul Muhakkamah rule in the decision. The research method used is normative legal research method with a qualitative approach. The qualitative approach was chosen to describe the research results with sentences that categorize the data according to certain categories. With this approach, the research can provide in-depth conclusions about the application of the Al'adatu Muhakkamah rule in the judge's decision. The research findings show that the judge should have granted the compensation claim based on the analysis of the al-'adatul muhakkamah rule. Islamic law aims to realize human welfare, including by recognizing that customs that are still valid for generations have a significant influence in determining legal decisions. However, the main principle of sharia must still be the top priority, especially if there is a conflict between custom and Islamic Law.